Interferon levels and interferon-stimulated gene expression identify patient subsets with distinct clinical and immunological characteristics in systemic lupus erythematosus - Khatri, Ridi; Jose, Amrutha; Rajadhyaksha, Anjali; Mehta, Kalpana; Nolkha, Nilesh; Kini, Seema; Nadkar, Milind; Jaiswal, Pooja; Pawar, Pratiksha; Pawaskar, Swapnal; S, Kavyasree; Das, Ajit Kumar; et al. (Frontiers in Immunology, 2026)
IntroductionInterferon(IFN) system is dysregulated in Systemic Lupus Erythematosus(SLE) and represents potential therapeutic target. However, most studies have focused on isolated IFN types, particularly type I and type II, while type III IFNs remain poorly characterized. Comprehensive analysis of different IFN types in parallel with interferon-stimulated gene(ISG) expression is limited despite the interconnectedness of IFN families and their potential to differentially influence disease activity, immune phenotypes, and treatment responses. The present study assessed levels of IFN types and IFN score to evaluate their association with disease activity, clinical manifestations, and autoantibody profile in SLE patients from Western India.MethodsThis cross-sectional study included clinically diagnosed SLE patients(n=115). Serum IFNα and IFNλ1-λ4 levels were detected using ELISA, while IFNγ levels were detected using bead-based assay, and IFN score by RT-qPCR based on the expression of five ISGs. SLE patients with IFN levels above third quartile were categorized as ‘IFN high’ groups, and their association with clinical and autoantibody profile were analysed using logistic regression. To identify patient subgroups based on autoantibody profile, unsupervised clustering was employed.ResultsSLE patients showed significantly elevated IFNα(p<0.001), IFNγ(p=0.009), and IFNλ3(p<0.001) levels as well as IFN score(p<0.001) as compared to healthy controls. IFN score(r=0.228;p=0.014) and IFNα levels(r=0.430;p<0.001) correlated positively with disease activity. IFNα high group was associated with leukopenia (OR(95%CI):5.81(1.29,26.20);p=0.022) and multiple autoantibodies, while IFNγ high group with rash (OR(95%CI):2.73(1.06,7.00);p=0.037). FNλ3 high group showed positive association with anti-Ro52 autoantibodies (OR(95%CI):2.64(1.07,6.52);p=0.035) and negative association with low complement (OR(95%CI):0.35(0.13,0.89);p=0.028). IFNλ4 levels were not significantly elevated in SLE patients(p=0.642), however the levels were significantly associated with IFN score(r=0.359,p<0.001) and anti-dsDNA positivity(r=0.323,p<0.001), with higher levels observed in IFN score high SLE patients(p=0.016). Autoantibody profile-based clustering identified three subgroups differing in IFNα levels, IFN scores, disease activity, and associated immunological parameters.ConclusionAll three IFN pathways were elevated in SLE. Correlation of IFNα levels and IFN score with SLEDAI suggested their potential as possible biomarker for monitoring disease activity. Association of IFNλ4 with IFN score suggested their possible role in IFN pathway activation.By assessing IFNs at both protein and transcriptional levels, present study provided comprehensive insight into IFN pathway dynamics and IFN-driven heterogeneity in SLE.